ARKAS: Implementation of Database System for the Development of Educational Report Platform in accordance with Permendiknas No 19 of 2007 - Era Dhika Safitri; Rudy Widyanarko; Purdiyanti; Nurkolis (Universitas Negeri Semarang, 2024)
Provisions in Presidential Regulation No. 57 of 2021 concerning Education Standards and Minister of National Education Regulation No. 19 of 2007 concerning Education Management Standards by Elementary and Secondary Education Units set standardized indicators for education management from elementary to secondary levels. One form of indicator is the relationship between education and the quality of educational reports. However, there is an issue of weak educational quality reports that vary and often lead to bias, resulting in planning that is merely focused on administrative document fulfillment rather than achieving the intended goals. The research focus is on developing a platform as a solution to the Education Report based on Minister of National Education Regulation No. 19 of 2007. The research method used is descriptive qualitative to examine how the newly launched Indonesian Education Report platform can be utilized in data-based education planning to ensure more targeted planning and enhance the quality of education. The analysis results indicate that the Education Profile and Report platforms of each education unit serve as empirical databases that will be used as the basis for the development of ARKAS. The provision of educational services within these data-based education units will be more optimal as they are based on data from each indicator achievement available on the Education Profile and Report platform.